Supply and demand perceptions of stakeholders on a nonprofit investigative journalism center at the UP College of Mass Communication - Santiago, Jessica Gabrielle Thea F. (2012)
"This study used one-on-one in-depth interviews with four professional investigative journalists, seven former undergraduate journalism students, one senior undergraduate journalism student, two full-time members of the journalism faculty and the college dean to determine the reactions of stakeholders toward establishing a nonprofit investigative journalism organization at the University of the Philippines College of Mass Communication (UP CMC). The envisioned organization was modelled after the Investigative Reporting Workshop at the American University and the New England Center for Investigative Reporting at Boston University. An integration of the Open Systems Theory and stakeholder's analysis framed this study's methodology. Sources reacted positively to the idea of an investigative journalism center at UP CMC. However, based on the interviews, the UP CMC journalism department will only work toward establishing the center if the current roster of journalism undergraduates show a keen interest in learning investigative journalism and if they show their mentors that they possess a strong background in at least basic news writing."